1993
DOI: 10.1063/1.353745
|View full text |Cite
|
Sign up to set email alerts
|

Modeling growth of Si1−xGex epitaxial films from disilane and germane

Abstract: A Langmuir-Hinshelwood-type kinetic model is developed for modeling growth of silicongermanium alloys from disilane and germane on Si substrates. Gas source molecular beam epitaxy was employed to grow Si,-,Ge, iilms at various germanium fractions, X, in the alloy and at different temperatures. The model correc.tly predicts experimentally observed and previously reported behavior; a monotonic decrease with germanium fraction at higher substrate temperatures (700 "C) and a maximum in the growth rate for lower te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…In the case of Si or Ge deposition on Si, the principal effect of H is the passivation of the Si surface dangling bonds, which leads to a decrease of the deposition rate of both Si and Ge. Consequently, the surface desorption of H during CVD growth is considered as the principal phenomenon driving the surfactant effect of H. [9][10][11][12][13][14] Kamins et al 15 studied the effects of P during CVD of Ge on Si(001), and showed that the co-deposition of P ͑PH 3 ͒ and Ge ͑GeH 4 ͒ leads to the formation of Ge islands with different shapes and smaller sizes than typical huts and domes, also finding a decreased deposition rate with higher PH 3 partial pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Si or Ge deposition on Si, the principal effect of H is the passivation of the Si surface dangling bonds, which leads to a decrease of the deposition rate of both Si and Ge. Consequently, the surface desorption of H during CVD growth is considered as the principal phenomenon driving the surfactant effect of H. [9][10][11][12][13][14] Kamins et al 15 studied the effects of P during CVD of Ge on Si(001), and showed that the co-deposition of P ͑PH 3 ͒ and Ge ͑GeH 4 ͒ leads to the formation of Ge islands with different shapes and smaller sizes than typical huts and domes, also finding a decreased deposition rate with higher PH 3 partial pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The diffusion model: It is known that H 2 , HCl, and SiCl 2 /GeCl 2 desorb faster from Ge than from Si ͑i.e., activation barriers for H 2 -desorption from Ge: 37 kcal/mol, [17][18][19] from Si: 47 kcal/mol͒. The diffusion model: It is known that H 2 , HCl, and SiCl 2 /GeCl 2 desorb faster from Ge than from Si ͑i.e., activation barriers for H 2 -desorption from Ge: 37 kcal/mol, [17][18][19] from Si: 47 kcal/mol͒.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, attempts to predict SiGe deposition have previously relied on phenomenological surface chemistry models with experimentally determined kinetic parameters interpolated from the pure components. [12][13][14][15][16] The effect of Ge on hydrogen desorption has motivated a number of experimental studies on both Ge-covered Si(100) [17][18][19][20][21] and SiGe alloy surfaces, [22][23][24] resulting in two proposed explanations for the effect of Ge on hydrogen desorption kinetics. The "long-range-electronic-effect model" attributes the decrease in activation barriers to electronic effects of Ge atoms on the surface, which weaken the Si-H bonds and thus decrease the activation barrier of hydrogen desorption.…”
Section: Introductionmentioning
confidence: 99%
“…Deposition of SiGe alloys is commonly achieved by chemical vapor deposition (CVD) or gas-source molecular beam epitaxy (GSMBE) with Si and Ge hydrides as gas-phase precursors. It is well-known that the presence of GeH 4 in a SiGe deposition source gas mixture enhances the growth rate of SiGe alloys compared to epitaxial Si growth, and the effect has been attributed to the enhanced hydrogen desorption rate when Ge is present on the surface during growth. However, the mechanism by which Ge alloying affects hydrogen desorption chemistry is still unclear. Therefore, attempts to predict SiGe deposition have previously relied on phenomenological surface chemistry models with experimentally determined kinetic parameters interpolated from the pure components. …”
Section: Introductionmentioning
confidence: 99%